The application of low cost GIS package for property valuation - Buyong, Taher; Ismail, Suriatini (UTM, 2001)
The comparison method of valuation has been the most acceptable method in property valuation particularly residential properties. The use of comparison method of valuation has involved the problems of inconsistency, inaccuracy, human fatigue, and time consuming. All these problems arise due to the massive amount of •comparables data involved in the valuation process. This situation can bring decremental effect to the quality of property value derived thus the poblems need to be addressed. GIS is a solution to the above problems. This has brought up a need for such a system as an aid in the valuation process based on the method of comparison. It has been the aim of this research to design a system for property valuation purposes based on GIS. Maplnfo, a low cost GIS is used for this research. The system developed is named VALGIS and has undergone a performance test which involved real estate data obtainable from JPPH, MBJB and CALS. The test shows that VALGIS has fulfilled the three criteria set out earlier: capable of carrying out valuation process, easy to use and can expedite the valuation process.